The Opportunities and Challenges in Using Virtual Anatomy - Yuliana, Yuliana (Proceeding International Conference on Religion, Science and Education, 2024)
The COVID-19 pandemic makes the lecturer and students adapt by using online classes. One of the methods of using online classes is by delivering the anatomy material in virtual classes (virtual reality, anatomy studio). This paper aims to describe the opportunities and challenges of using virtual anatomy. This is a narrative literature review. Literature was taken from PubMed, Google Scholar, and Science Direct. The selected articles were published within 5 years. The opportunities of using virtual anatomy are students can access the material anywhere and anytime, while lecturers can give the materials of the study anywhere and anytime. The challenge is that virtual anatomy is not as perfect as 3D anatomy (cadaveric section) in giving the real anatomy sensation to the students. Therefore, virtual anatomy should be seen as an add-on for the anatomy study. In conclusion, although it is not as complete as the cadaveric section, virtual anatomy gives new opportunities for learning anatomy anywhere and anytime for students and lecturers.